Peran Dinas Perdagangan dan Perindustrian (Disperdagin) dalam Menjaga Stabilitas Harga Cabai di Pasar Bintan Center Kota Tanjungpinang - Nadilla Nadilla; Widia Ierdiana (Fakultas Teknik Universitas Cenderawasih, 2024)
This research examines the role of the Department of Trade and Industry (Disperdagin) in maintaining the stability of chili prices at the Bintan Center Market, Tanjungpinang City, using qualitative methods, collecting data sourced from official news sites, interviews with related parties, and from journal articles. Price instability and unsmooth distribution of chilies are problems that require evaluation of the role of Disperdagin in monitoring and maintaining price stability so that significant increases do not occur. The research results show that the Tanjungpinang City Disperdagin has a complex role in maintaining chili price stability. Apart from functioning as a supervisor and regulator of trade activities, Disperdagin is responsible for ensuring that the distribution mechanism runs smoothly and efficiently, and that the prices set remain affordable for the local community. However, implementing this role often faces obstacles, such as limited resources and unexpected price fluctuations. To overcome these challenges, Disperdagin collaborates with the Tanjungpinang City Government through various activities such as meetings, inspections, supervision, organizing cheap markets, and providing subsidies for transportation costs for sending chilies.